2021
DOI: 10.1017/s0952675721000038
|View full text |Cite
|
Sign up to set email alerts
|

Phonological contrasts and gradient effects in ongoing lenition in the Spanish of Gran Canaria

Abstract: This study explores ongoing lenition of postvocalic /p t k b d g/ in the Spanish of Gran Canaria. Duration, intensity and harmonics-to-noise ratio of 16,454 sounds produced by 44 native speakers were measured, with the latter phonetic parameter used for the first time to investigate lenition. The results show a path of gradual sound shortening and opening from voiceless stops to open approximants, as well as systematic use of six different variants depending on the underlying representation and phonological co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 42 publications
4
19
0
Order By: Relevance
“…Kirchner 1998: ch 4, Lavoie 2001. This is now well established for Spanish (Romero Gallego 1995, Cole et al1998, Ortega-Llebaria 2003, Kingston 2008, Figueroa Candia 2016, Broś et al 2021, and we will see below that the same goes for Ibibio.…”
Section: The Main Lenition Typessupporting
confidence: 61%
See 4 more Smart Citations
“…Kirchner 1998: ch 4, Lavoie 2001. This is now well established for Spanish (Romero Gallego 1995, Cole et al1998, Ortega-Llebaria 2003, Kingston 2008, Figueroa Candia 2016, Broś et al 2021, and we will see below that the same goes for Ibibio.…”
Section: The Main Lenition Typessupporting
confidence: 61%
“…Various methods have been proposed elsewhere for measuring the effect of lenition on the intensity properties of consonants, especially in Spanish. One method measures the difference in intensity between a consonant and a neighbouring vowel (Soler & Romero 1999, Lavoie 2001, Ortega-Llebaria 2004, Colatoni & Mainsescu 2010, Hualde et al 2011, Carrasco et al 2012, Broś et al 2021. Another measures the velocity with which intensity increases between the consonant and a following vowel, motivated by the observation that C-to-V transitions are more abrupt when the consonant is a stop than 10 The speech data on which this section is based were originally collected for a study reported by Harris & Urua (2001).…”
Section: Edge: Methodsmentioning
confidence: 99%
See 3 more Smart Citations